2016
DOI: 10.1504/ijqre.2016.073633
|View full text |Cite
|
Sign up to set email alerts
|

Preschool attendance: a multilevel analysis of individual and community factors in 21 low and middle-income countries

Abstract: This paper investigates how preschool attendance is shaped by individual and community factors for 71,806 children from 14,303 communities in 21 low-to middle-income countries using a multilevel analysis. We assess how these mechanisms vary by community and country wealth and the extent to which the variation of preschool attendance can be explained by the characteristics of children living in these communities. We find that of the total variation, 36% was attributable to communities and 12% to countries, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These findings are consistent with one study from Uruguay that reported that one third of children enrolled in preschool were absent for more than 15% of school days (Díaz et al, 2020). Data from around the world about daily attendance by preschoolers is scant (most studies have focused on preschool attendance as a binary variable, more reflective of preschool access and uptake; Gong et al, 2015;Boo, 2016;Delprato et al, 2016;Woldehanna, 2016;Sun et al, 2018;Su et al, 2020). This study and emergent literature suggest that levels of absences among children enrolled in early childhood education in the global majority may be high and reinforces that efforts to achieve the United Nation's Sustainable Development Goal 4.2 (i.e., by 2030, ensure that all children have access to quality early childhood development, care and pre-primary education so they are prepared for primary education) should include attention to attendance promotion and absenteeism prevention (UN General Assembly, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with one study from Uruguay that reported that one third of children enrolled in preschool were absent for more than 15% of school days (Díaz et al, 2020). Data from around the world about daily attendance by preschoolers is scant (most studies have focused on preschool attendance as a binary variable, more reflective of preschool access and uptake; Gong et al, 2015;Boo, 2016;Delprato et al, 2016;Woldehanna, 2016;Sun et al, 2018;Su et al, 2020). This study and emergent literature suggest that levels of absences among children enrolled in early childhood education in the global majority may be high and reinforces that efforts to achieve the United Nation's Sustainable Development Goal 4.2 (i.e., by 2030, ensure that all children have access to quality early childhood development, care and pre-primary education so they are prepared for primary education) should include attention to attendance promotion and absenteeism prevention (UN General Assembly, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…Women's individual responses were nested in communities. Communities were represented by DHS primary sampling units of about 20–200 people because they are the most consistent measure of community between DHS data sets and have been used to represent community in a number of multilevel studies using DHS data .…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with one study from Uruguay that reported that one third of children enrolled in preschool were absent for more than 15% of school days (Díaz et al, 2020). Data from around the world about daily attendance by preschoolers is scant (most studies have focused on preschool attendance as a binary variable, more reflective of preschool access and uptake; Gong et al, 2015;Boo, 2016;Delprato et al, 2016;Woldehanna, 2016;Sun et al, 2018;Su et al, 2020). This study and emergent literature suggest that levels of absences among children enrolled in early childhood education in the global majority may be high and reinforces that efforts to achieve the United Nation's Sustainable Development Goal 4.2 (i.e., by 2030, ensure that all children have access to quality early childhood development, care and pre-primary education so they are prepared for primary education) should include attention to attendance promotion and absenteeism prevention (UN General Assembly, 2015).…”
Section: Discussionmentioning
confidence: 99%